Comparison of Flour Starch Properties in Half‐Sib Families of Opaque‐2 Maize (Zea mays L.) from Argentina. Issue 6 (25th August 2017) - Mansilla, Pablo Sebastián; Nazar, María Cristina; Pérez, Gabriela Teresa
Abstract : Since the discovery of the o2 mutation in maize, many studies have reported the characterization of the protein quality of opaque‐2 genotypes. However, few have reported the properties of their starch. The objective of this study was to characterize flour starch properties of 12 half‐sib families of opaque‐2 maize from Argentina. Chemical composition and thermal and pasting properties of whole grain flour were determined. Nonopaque genotypes were used as a control. Starch content of opaque‐2 genotypes did not show significant differences compared with nonopaque genotypes, yet amylose content was significantly lower. A high variability in pasting and thermal properties was observed in genotypes. Opaque samples showed a significantly higher peak viscosity and a lower pasting temperature compared with nonopaque samples, probably owing to larger and less compact starch granules in the floury endosperm. The higher the gelatinization enthalpy of opaque‐2 genotypes was, the lower the amylose content in relation to nonopaque varieties. Two retrogradation endotherms were observed in DSC analysis: one corresponding to amylopectin crystallization and the other to melting of amylose‐lipid complex. Both enthalpies were considered total starch retrogradation (Δ H RT ). A wide range of variation was obtained in Δ H RT in opaque‐2 genotypes, but no significant differences between opaque and nonopaque genotypes were observed. The differences in starch properties found in this study would make it possible to identify opaque‐2 families with particular characteristics for the development of starchy food items adapted to specific processing traits.